Media Gerak dan Lagu dalam Menanamkan Nilai-nilai Agama dan Moral pada Anak Usia Dini - Muchsinun, Amalia; Robingatin, Robingatin; Afendi, Achmad Ruslan (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This research is motivated by the importance of instilling religious and moral values in children to protect them from the threat of moral degradation that occurs along with modernization. To achieve this goal, one of the approaches used is learning to use motion media and songs. This study aims to discover the stages passed and the benefits of using motion media and songs in learning to instill religious and moral values in early childhood. The type of research used in this research is qualitative with a case study approach. The location of this research is in Al-Hikmah Kindergarten and Al-Quds Kindergarten, Samarinda City. Data collection techniques used are interviews, observation, and documentation. The data analysis technique used is a single-site analysis by condensing data, making data displays, and verifying and drawing conclusions. The results showed that at TK Al-Hikmah, the planning stage was carried out by recruiting teachers who were competent and had a strong Islamic background. The implementation stage is carried out by singing songs about getting to know angels, getting to know the 25 Prophets, and getting to know the obligatory nature of Allah. The results obtained in the kindergarten are forming new positive behaviors or habits in children. As for the Al-Quds Kindergarten, the planning stage is carried out by strictly selecting teachers and preparing songs to be sung with children. The implementation stage is carried out by singing songs that recognize body parts and prepositions in Arabic and clap ablution. The perceived benefits are that it can stimulate children's motor movements and help to introduce religious and moral aspects to children.